PENGARUH LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA - Dewi Saputri; Rahmadifa; Siti Zarina (JIP: Jurnal Ilmu Pendidikan, 2026)
Student learning achievement is one of the key indicators of educational success and is influenced by various internal and external factors. One important external factor is the family environment. This study aims to describe the condition of the family environment in supporting students’ learning activities, analyze students’ learning achievement at school, and examine the influence of the family environment on students’ learning achievement. This research employed a qualitative approach using a case study design. The research subjects were selected purposively and involved students, parents, and teachers. Data were collected through in-depth interviews, observations, and documentation. The data were analyzed thematically through data reduction, data presentation, verification, and conclusion drawing, supported by source triangulation to ensure data validity. The results indicate that a supportive family environment characterized by harmonious relationships, parental attention, learning assistance, and adequate learning facilities has a positive effect on students’ learning achievement. Conversely, a lack of parental attention, limited economic conditions, and an unconducive home environment negatively affect students’ motivation and academic achievement. Therefore, it can be concluded that the family environment has a significant influence on students’ learning achievement and that collaboration between families and schools is essential to support students’ learning success.